Informality as a stepping stone: entrepreneurial entry in a developing economy - John Bennett; Saul Estrin (Institute for the Study of Labor (IZA), 2007)
We model decisions with respect to formality or informality for entrepreneurs in a new industry for a developing economy. We show that informality allows a leader to explore, without significant sunk costs, the potential profitability of the industry; that is, informality may be a stepping stone, enabling an entrepreneur to experiment cheaply in an uncertain environment. There are circumstances under which, without this option, the industry would not become established. We analyse the roles of parameters such as a minimum wage rate and we show that the existence of finance constraints can actually encourage entry in this context.
Keywords: 330; Unternehmensgründung; Informeller Sektor; Markteintritt; Entwicklungsländer